Characteristics, challenges and innovations of waste picker organizations: A comparative perspective between Latin American and East African countries - Kain, Jaan Henrik (2022)
Waste picker organisations (WPOs) around the globe collect, transport and process waste to earn their living but represent a widely excluded, marginalised and impoverished segment of society. WPOs are highly innovative, created by grassroots out of "nothing"to deliver economic, social and environmental sustainability. Still, we do not know how such innovations are developed, and how they are disseminated and adopted by other groups. This article examines characteristics, challenges and innovations of WPOs across five countries in Latin America and East Africa. It is based on quantitative and qualitative data regarding modes of organisation and management, gender, received support, business orientations, environmental and social contributions, and innovations developed in response to multiple challenges. The paper provides a comprehensive understanding of WPOs' activities and their grassroots innovations in the Global South. The study shows how WPOs contribute significantly to the economic, social and environmental sustainability of the societies they serve as well as the wider urban societies. To start and maintain WPOs in informal settlements with a lack of infrastructure, institutional frameworks, and public and private investors is a difficult quest. WPOs take many different organisational forms depending on the complexity of local realities, ranging from advanced collective organization as cooperatives to small self-help groups and microentrepreneurs. Selforganisation into regional and national networks provides economic opportunities, autonomy and stability as well as political influence. Yet, institutional support is fundamental and the lack thereof threatens their existence. Sustaining WPOs as important providers of socio-environmental benefits through governmental and non-governmental actions is a worthwhile undertaking that builds sustainability.